Laboratory measurements of the viscous anisotropy of olivine aggregates. - Hansen, L; Zimmerman, M; Kohlstedt, D (2012)
A marked anisotropy in viscosity develops in Earth's mantle as deformation strongly aligns the crystallographic axes of the individual grains that comprise the rocks. On the basis of geodynamic simulations, processes significantly affected by viscous anisotropy include post-glacial rebound, foundering of lithosphere and melt production above subduction zones. However, an estimate of the magnitude of viscous anisotropy based on the results of deformation experiments on single crystals differs by three orders of magnitude from that obtained by grain-scale numerical models of deforming aggregates with strong crystallographic alignment. Complicating matters, recent experiments indicate that deformation of the uppermost mantle is dominated by dislocation-accommodated grain-boundary sliding, a mechanism not activated in experiments on single crystals and not included in numerical models. Here, using direct measurements of the viscous anisotropy of highly deformed polycrystalline olivine, we demonstrate a significant directional dependence of viscosity. Specifically, shear viscosities measured in high-strain torsion experiments are 15 times smaller than normal viscosities measured in subsequent tension tests performed parallel to the torsion axis. This anisotropy is approximately an order of magnitude larger than that predicted by grain-scale simulations. These results indicate that dislocation-accommodated grain-boundary sliding produces an appreciable anisotropy in rock viscosity. We propose that crystallographic alignment imparts viscous anisotropy because the rate of deformation is limited by the movement of dislocations through the interiors of the crystallographically aligned grains. The maximum degree of anisotropy is reached at geologically low shear strain (of about ten) such that deforming regions of the upper mantle will exhibit significant viscous anisotropy.